Molecular characterization of group A rotavirus from rhesus macaques (Macaca mulatta) at human–wildlife interfaces in Bangladesh. Issue 2 (10th December 2019) - Islam, Ariful; Hossain, Mohammad Enayet; Haider, Najmul; Rostal, Melinda K.; Mukharjee, Sanjoy Kumar; Ferdous, Jinnat; Miah, Mojnu; Rahman, Mustafizur; Daszak, Peter; Rahman, Mohammed Ziaur; Epstein, Jonathan H.
Abstract: Group A rotavirus (RVA) is an important cause of diarrhoea in people, especially children, and animals globally. Due to the segmented nature of the RVA genome, animal RVA strains have the potential to adapt to the human host through reassortment with other co‐infecting human viruses. Macaques share food and habitat with people, resulting in close interaction between these two species. This study aimed to detect and characterize RVA in rhesus macaques ( Macaca mulatta ) in Bangladesh. Faecal samples ( N  = 454) were collected from apparently healthy rhesus macaques from nine different sites in Bangladesh between February and March 2013. The samples were tested by one‐step, real‐time, reverse transcriptase‐polymerase chain reaction (PCR). Four percent of samples ( n  = 20; 95% CI 2.7%–6.7%) were positive for RVA. RVA positive samples were further characterized by nucleotide sequence analysis of two structural protein gene fragments, VP4 (P genotype) and VP7 (G genotype). G3, G10, P[3] and P[15] genotypes were identified and were associated as G3P[3], G3P[15] and G10P[15]. The phylogenetic relationship between macaque RVA strains from this study and previously reported human strains indicates possible transmission between humans and macaques in Bangladesh. To our knowledge, this is the first report of detection and characterization of rotaviruses in rhesus macaques in Bangladesh. These data will not only aid in identifying viral sharing between macaques, human and other animals, but will also improve the development of mitigation measures for the prevention of future rotavirus outbreaks.